Social Protection Responses to the Global Economic Crisis in ECA - Lindert, Kathy; Schwarz, Anita (World Bank, Washington, DC, 2012)
Besides affecting the private sector, the current global economic downturn will likely have a far-reaching impact on government revenues around the world. As country budgets are squeezed tight, social programs which directly help poor and vulnerable people will become pressure points for reducing government spending. In many countries in Eastern Europe and Central Asia (ECA), two years of rising food prices, high energy costs and the global economic downturn have combined with other shocks like natural disasters and political instability. The impacts of these crises could reduce government revenues and affect social spending and pension systems, even as the need for unemployment and benefits increases. In the short run, ECA countries may call on the World Bank to provide financial or technical support to help with the immediate impacts of the crises. Rapid support could include: (a) helping countries finance temporary scaling-up of well-targeted safety nets, either in beneficiary coverage or with a topping-up of benefits values; and (b) supporting actions to protect the budgets of well-targeted programs and other crucial spending on education and health. Governments and the Bank need to be prepared to respond more adeptly in the future; safety nets are important not only in times of crises but, in the long-run, they help to protect the poor and allow governments to avoid other, more costly or inefficient policies.